Організаційно-фінансових механізм забезпечення фінансово-економічної безпеки банківської системи - Рязанова, Н. О.; Riazanova, N. O. (Видавництво Львівської політехніки, 2021)
Запропоновано організаційно-фінансовий механізм забезпечення фінансово-економічної безпеки банківської системи, який дає змогу мінімізувати потенційні ризики та зміни внутрішньофірмового інституційного середовища. Особливістю механізму є застосування методів стратегічного управління для формування економічних ресурсів, підвищення іміджу та рівня безпеки інформаційних систем, що створить умови для забезпечення належного рівня захищеності від негативних факторів та загроз та підвищення конкурентоспроможності банку внаслідок підвищення оперативності надання банківських послуг, збереження банківської таємниці та клієнтської бази, створення нових банківських продуктів.

An organizational and financial mechanism for ensuring the financial and economic security of a commercial bank is proposed, which, in real time and in situations that cannot be controlled using traditional methods, will minimize potential risks and change the internal institutional environment, positively affecting the financial and economic security of the country’s banking system. It is shown that economic growth as a factor of national security is supported by the effective functioning of the banking system and the priority of long-term bank loans provided in the form of investments, which makes it possible to determine the relationship between the growth of the country’s economy and the level of financial and economic security of the banking system. The main approaches to ensuring the financial and economic security of the banking system are considered, which include the structure of the primary interests of a commercial bank and indicators of the level of financial and economic security of the banking sector of Ukraine in order to ensure economic stabilization and strengthen the economic potential of the bank. It was noted that an adequate and fundamental marketing strategy will help to promote the growth of the bank’s profitability, attract additional customers, form a resource base and reduce risk in banking. Mortgage lending is considered as the most effective tool for attracting funds from the population to the investment sector and meeting their needs for housing. A distinctive feature of the presented organizational and financial mechanism is the use of strategic management methods to form economic resources, improve the image and level of security of information systems, organize effective management of the bank’s personnel, which will create conditions for ensuring the proper level of protection against negative factors and threats and increasing the competitiveness of the bank due to increasing the efficiency of the provision of banking services, preserving banking secrecy and the client base, creating new banking products.
Organizational and financial mechanism for ensuring financial and economic security of the banking-system
Keywords: організаційно-фінансовий механізм; фінансово-економічна безпека; банківська система; маркетингова стратегія; банківські ризики; іпотечне кредитування; organizational and financial mechanism; financial and economic security; banking system; marketing strategy; banking risks; mortgage lending; 336.7